Current Topics in Innate Immunity - Lambris, John D.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2007)
Innate Immunity has long been regarded as the non-specific arm of immune response, acting immediately and in a generic way, to defend the host from infections. In the post genomic era, our knowledge of the innate immune system is enriched by findings on the specificity of innate immune reactions as well as to novel functions that do not strictly correlate with immunological defense and surveillance, immune modulation or inflammation. Several studies indicate that molecules involved in innate immunity exert functions that are either more complex than previously thought, or go well beyond the innate immune character of the system. The advent of high-throughput platforms for genome and proteome-wide profiling, together with the enormous amount of raw genetic information that has accumulated in the databases, have stirred new expectations in biomedical research. They have led scientists to revisit established biological systems from a global and integrative perspective. Innate Immunity research is now faced with the challenge of trying to integrate isolated biochemical pathways into complex gene and protein regulatory circuits. In this respect, scientists from around the world convened at the 4th International Conference on Innate Immunity (June 4 - 9, 2006), in Corfu, Greece to discuss recent advances in this fast evolving field. This volume represents a collection of topics on natural killer cells, mast cells, phagocytes, toll like receptors, complement, host defense in plants and invertebrates, evasion strategies of microorganisms, pathophysiology, protein structures, design of therapeutics, and experimental approaches discussed during the conference.
Toll-like Receptors, Natural Killer Cells and Innate Immunity -- In the Thick of the Fray: NK Cells in Inflamed Tissues -- Structural Insight into Natural Killer T Cell Receptor Recognition of CD1d -- The Journey of Toll-like Receptors in the Cell -- Differential Regulation of Key Signaling Molecules in Innate Immunity and Human Diseases -- Systems Biology of Macrophages -- The Alternative Pathway of Complement: a Pattern Recognition System -- Role of MBL-associated Serine Protease (MASP) On Activation of the Lectin Complement Pathway -- Viral Heparin-Binding Complement Inhibitors – A Recurring Theme -- C3a Receptors Signaling in Mast Cells -- Antimicrobial C3a –Biology, Biophysics, and Evolution -- C5L2 – an Anti-inflammatory Molecule or a Receptor for Acylation Stimulating Protein (C3a-desArg)? -- The Exosporium of B.cereus Contains a Binding Site for gC1qR/p33: Implication in Spore Attachment and/or Entry -- Immunity in Borreliosis with Special Emphasis on the Role of Complement -- Murine CR1/2 Targeted Antigenized Single-Chain Antibody Fragments Induce Transient Low Affinity Antibodies and Negatively Influence an Ongoing Immune Response -- The Third Complement Component as Modulator of Platelet Production -- In Vivo Biological Responses in the Presence or Absence of C3 -- Complement Activation of Drusen in Primate Model (Macaca fascicularis) for Age-Related Macular Degeneration -- Exploring the Complement Interaction Network Using Surface Plasmon Resonance -- Glycosylation as a Target for Recognition of Influenza Viruses by the Innate Immune System -- Immune Effects of Autoantigen-Associated RNA -- Induction and Evasion of the Type I Interferon Response by Cytomegaloviruses -- Pore Formers of the Immune System -- Pathogen-Specific Innate Immune Response -- Flagellin Signalling in Plant Immunity -- Ancient Origin of the Complement System: Emerging Invertebrate Models -- Biological Roles of Lectins in Innate Immunity: Molecular and Structural Basis for Diversity in Self/Non-Self Recognition -- Hydrogen/Deuterium Exchange Mass Spectrometry:Potential for Investigating Innate Immunity Proteins.
Keywords: Immunology; Microbiology; Infectious diseases; Immunology; Microbiology; Infectious Diseases